FATTY ACID COMPOSITION OF PRECANCEROUS CERVICAL LESIONS AND CERVICAL CANCER TISSUES - ELENA V. Kayukova; TATIANA E. Belokrinitskaya; LEONID F. Sholokhov; PAVEL P. Tereshkov (Фундаментальная и клиническая медицина)
Aim. To determine the fatty acid composition of lipids extracted from precancerous lesions and malignant tumors of the cervix. Materials and Methods. We first isolated segments from precancerous cervical lesions and cervical cancer along with adjacent normal tissues. Extraction of lipids from homogenized tissues was performed employing Folch method. Fatty acid composition was evaluated utilizing gas-liquid chromatography. Results. Both precancerous and malignant cervical lesions demonstrated higher levels of saturated and odd-chain fatty acids while having lower levels of mono- and polyunsaturated fatty acids in comparison with adjacent normal tissues. We also detected an increased amount of nonadecylic/ nonadecanoic acid (C19:0) in cancerous tissues as compared to both precancerous lesions and healthy cervix. Conclusions. Cervical cancer cells are characterized by an impaired lipid metabolism.